2020
DOI: 10.3390/w12082206
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship among Precipitation, Application of Salt in Winter Road Maintenance and the Quality of Waterways and Soil around Motorway

Abstract: Construction of motorways and road traffic bring a new line element into the landscape, which fundamentally influences the local hydrological regime and water quality. Impermeable surfaces are introduced into the landscape, affecting the natural infiltration of water in the environment. The aim of the present research was to assess the long-term historical development of changes in the landscape retention potential due to construction of the D1 motorway in the Jihlava region and also evaluate the impact of win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…The remaining months were characterized by lower concentrations. According to the literature, the highest concentrations of Na, Cl, and K occur most often in the summer months, which is associated with low precipitation and high temperatures [ 68 , 69 ]. Our research supports this relationship; however, in addition, we observed several factors that disrupted the seasonal pattern and caused inter-annual differences.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining months were characterized by lower concentrations. According to the literature, the highest concentrations of Na, Cl, and K occur most often in the summer months, which is associated with low precipitation and high temperatures [ 68 , 69 ]. Our research supports this relationship; however, in addition, we observed several factors that disrupted the seasonal pattern and caused inter-annual differences.…”
Section: Resultsmentioning
confidence: 99%
“…This helps to increase safety on roads in winter, as well as assisting with troubleshooting of roadworthiness, and providing an outlet for the ecological disposal of magnesium chloride. However, elements contained in spreading materials enter the air, water, and soil, affecting their natural state [ 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the substances used for ice prevention and removal, sodium chloride (NaCl) and calcium chloride (CaCl 2 ) are the most commonly used, and the criteria for using one or the other is determined by the minimum temperature. Sodium chloride is used at temperatures as low as −5 • C and calcium chloride is used when temperatures are even lower [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Sustainability 2021, 13, 5392 2 of 16 In addition, when the ice is formed, machines are sometimes needed for its removal, causing a serious deterioration in the asphalt pavement.…”
Section: Introductionmentioning
confidence: 99%